The Influence of Hard Skills and Soft Skills on Work Readiness Through Self-Efficacy as an Intervening Variable in Students - Rutnauli Butar-butar; Tony Wijaya (International Journal of Humanities and Social Sciences Reviews, 2025)
This study aims to analyze the influence of hard skills and soft skills on job readiness through self-efficacy as a mediating variable in students at the Faculty of Economics and Business, Yogyakarta State University. The background of the study is rooted in the increasing demands of the job market, which emphasize not only technical competence but also interpersonal skills and individual confidence in their own capabilities. As the world of work becomes increasingly competitive, the ability to balance technical skills with psychological readiness becomes a crucial factor. This study employed a quantitative approach with descriptive analysis and path analysis. A total of 229 respondents were selected using a two-stage random sampling method to ensure adequate representation. The data were analyzed using SmartPLS to test the validity, reliability, and fit of the structural model. The results revealed that hard skills had a significant but negative effect on job readiness, while soft skills showed a positive but statistically insignificant effect. Both hard and soft skills were shown to have a positive and significant effect on self-efficacy, with self-efficacy having a significant effect on job readiness. Further findings indicate that self-efficacy mediates the relationship between hard skills and job readiness, but not the relationship between soft skills and job readiness. Overall, this research emphasizes the importance of integrating hard skills, soft skills, and self-efficacy in building student job readiness. The implication is that universities need to design curricula and student development programs that not only strengthen technical competencies but also foster interpersonal skills and self-confidence so that graduates can compete in a dynamic job market.